MENINGKATKAN KEMANDIRIAN SISWA DALAM PEMBELAJARAN BAHASA MELALUI PEMBELAJARAN BERBASIS KOMPUTER COMPUTER ASSISTED LANGUAGE LEARNING (CALL) - Wulandari, Ella (MAJALAH ILMIAH PEMBELAJARAN, 2008)
In addition to that, learner's autonomy indicated by learner's ability incollaborating with peers independently brings significant effect onmaximizing the zone of proximal development of the learner 's. The zoneof proximal development is at its best when learner is able to acquirelanguage input which is a step beyond his present languagecompetence. Despite those two huge benefits of developing /earner'sautonomy, teacher Â·sÂ· centredness has still, unfortunately, beendominating the teaching and learning practices in Indonesian schools.One of the effective attempts to reduce teacher's centredness and buildlearner's and teacher's autonomy is Computer Assisted LanguageLearning (CALL). By considering the principles in bui!ding learner'sautonomy and the characteristics of CALL, this paper is aimed athighlighting the significant correlation between /earner's autonomyand CALL and the possibilities or criteria in combining the two so as 10create an effective language teaching in classroom.